Síntese de novos derivados aminoquinolínicos com potencial atividade antimalárica - Almeida, Marta Maria Farias de Sousa (2014)
Malaria is responsible for a high morbidity and mortality of people worldwide, especially in tropical countries, with 3,4 billion individuals at risk of disease. Due to the resistance that some species have acquired in relation to drugs, particularly chloroquine, mainly for Plasmodium falciparum, it is necessary the development of new antimalarial agents active against these resistant strains. This work aims at obtaining new 4-aminoquinoline derivatives with potential antimalarial action. Four of this compounds derivatives were synthesized, having as source of inclusion of these pharmacophoric moiety(important for activity against malaria), the reagent 4,7-dichloroquinoline (DC) modified by Nucleophilic Aromatic Substitution reactions (SNAr). All compounds were isolated with moderate to good yields, namely: 7-chloro-N-(prop-2-ynyl)quinolin-4-amine (PCQ) with a yield of 92%, 7-chloro-N-(4-(diethylamino)but-2-ynyl)quinolin-4-amine (DAQ) having achieved a yield of 40%, N-(2-aminoethyl)-7-chloroquinolin-4-amine (CEQ) with 73% yield and 2-(7-chloroquinolin-4-ylamino)acetic acid (GIQ) with a 42% yield; PCQ was obtained from the reaction of CD with propargylamine. DAQ was obtained reacting formaldehyde, diethylamine, and PCQ. The reaction between DC and ethylenediamine under reflux gave CEQ. Finally, GIQ was obtained from a mixture of DC, glycine and phenol. All synthesized compounds were characterized by Nuclear Magnetic Resonance Spectroscopy 1H and 13C, and Infrared Spectroscopy and Melting Point. Effective quantification of antimalarial activity of these compounds is being evaluated.